A Comparative Study Between The Effect Of Summarizing And DRTA Strategies On Students’ Reading Comprehension - Ani Purnama Sari; Wisma Yunita; Alamsyah Harahap (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2020)
Abstract: A Comparative Study Between The Effect Of Summarizing And DRTA Strategies on Students’ Reading Comprehension. Reading is an action that urges learner to draw in with the writings so as to fabricate significance, handle the primary thoughts, realities, and data introduced in the text. This study aimed to compare the effectiveness of two strategies, i.e., Summarizing and DRTA (Directed Reading Thinking Activity) Strategies. This study was carried out at the tenth- grade students of SMA Negeri 9 Kota Bengkulu. The design was a quasi-experiment. The sample consisted of two classes; one was taught by summarizing strategy and another by DRTA strategy. The instrument was a reading test, which was tried-out; the reliability was 0.880 (very high). The hypotheses testing result showed there was no significant difference between both classes on all aspects and at post-test, there was no significant difference in whole reading comprehension, on the aspect of making inference and vocabulary. However, summarizing strategy was found to be more effective on the aspect of finding the main idea with the statistical value was 0.002 while DRTA strategy was found to be a more effective strategy on the aspect of identifying specific information with the statistical value was 0.000.